A systems biology approach to oncology drug development - Schoeberl, Birgit (Henry Stewart Talks, 2015)
Oncology drug development, Network biology, The HRG family of ligands, The ErbB pathway, MM-121 mechanism of action, Data from in-vitro and iv-vivo experiments using MM-121, Timeline of MM-121: 2003-2015